Knowledge sharing initiatives in Malaysian quantity surveying firms: What are the promoting factors and challenges? - Mohamed, Othman; Nor, Fadhilah Mohd; Hanid, Mahanim; Kho, Mei Ye; Othman, Maznah (Construction Research Institute of Malaysia, 2018)
Knowledge Management (KM) has attracted much attention in the construction industry especially with the emergence of the knowledge economy and is also one of the most significant current issues in the construction industry. Thus, the primary aims of this study are to: i) investigate the factors that promote knowledge sharing initiatives in Malaysian quantity surveying (QS) firms and ii) determine the challenges faced by Malaysian QS firms when implementing knowledge sharing initiatives. This study also investigated whether the size of the QS firm affected the factors that promote knowledge sharing initiatives and influenced the challenges faced by these firms. Responses from two hundred and eighty-two (282) quantity surveyors from three hundred and six (306) QS firms were analysed in this quantitative survey. The QS firms were classified into two (2) groups, i.e. small (less than 50 employees) and medium (50 to 250 employees) sized QS firms. The survey (postal, email and web) was derived and developed from semi-structured interviews involving twenty quantity surveyors. The Cronbach alpha (α) values of the 20 items in the questionnaire ranged from 0.813 to 0.872, indicating that the data were reliable. Findings from this study suggest that i) senior management support is the greatest influencing factor to promote knowledge sharing initiatives, ii) the size of QS firms impacted the factors that promote knowledge sharing initiatives, and iii) the size of the QS firm influenced the challenging factors associated with knowledge sharing initiatives. It is recommended that future studies explore the inhibiting factors and organisational readiness when implementing knowledge sharing initiatives.